Pendampingan Kewirausahaan: Penata Kelembagaan UMKM di Kecamatan Siantar Martoba Kota Pematangsiantar - Hengki Mangiring Parulian Simarmata; Henry Dunan Pardede; Poltak Pardamean Simarmata; Doris Yolanda Saragih (Jurnal Nusantara Berbakti, 2024)
Institutional administrators have an important role in developing MSME businesses in Indonesia. The role of institutional administrators is to encourage business actors to obtain training support, financial access and market access by strengthening cooperation between Government, financial institutions and non-governmental organizations. This activity aims to provide business actors in Siantar Martoba District with an understanding of the formation of business institutions being pursued. The activity method is carried out by planning, implementing and evaluating activities. The activity was carried out using a seminar model, which was attended by 31 participants who were livestock and weaving business people in Siantar Martoba District. Evaluation of the activity showed that 95% of participants felt the benefits of the activity and provided new insight into the importance of institutional arrangements to gain access to support from various parties